Implementasi Penentuan Harga Pokok Produksi dengan Metode Full Costing dan Activity Based Costing di UMKM Pabrik Krupuk Poli UD. Bhakti Rantani Sumenep - Nihayatut Tasliyah; Yulissaroh Yulissaroh; Khoirul Anwar (Jurnal Multidisiplin Ibrahimy, 2024)
Not a few MSMEs use traditional methods in determining product prices, so that the profits achieved are felt to have not met the aspect of justice. What they express is that the important thing is not to lose. The full Costing and Activity Based Costing methods are approaches that have been used by companies, the impact is that they can provide wages or services to all parties or elements involved in production or business. Because implementing the two methods is an effort to fulfill the rights of each element that has contributed to each business unit.